Eksperyment somatyczno-dramaturgiczny. Haptyczna wizualność i deziluzyjna dramaturgia w filmie Czarny Łabędź Darrena Aronofsky’ego - Woroch , Adrianna (Przestrzenie Teorii, 2021)
Based on the example of Darren Aronofsky’s film Black Swan, the article explores the disillusive potential of interfering with the classic model of film dramaturgy. Referring to the traditional paradigm developed by Syd Field, the author indicates deviations from the conventional narrative that occur in Aronofsky’s film. The text seeks to confirm the thesis that contemporary cinematography exemplifies the trend of abandoning the attempts to create a seemingly referential world. By questioning the fundamental structure of the film’s dramaturgy, Black Swan provides additional interpretive possibilities. However, displaying the constituent elements of a work, for example, by transaccentuating their meaning or changing their place or length of occurrence, is not the most obvious disillusionment strategy. It may in fact remain hidden until the moment of careful analysis.